ANALISIS CO BENEFIT DI SENTRA INDUSTRI TAHU ADIWERNA, KABUPATEN TEGAL - Hernaningsih, Taty (Jurnal Air Indonesia, 2010)
Ã¢â‚¬Å“Co-benefitsÃ¢â‚¬Â refers to multiple benefits in different fields resulting from one policy, strategy or action plan.Ã‚Â  As an example: policy or strategy taken on reducing GHG emission from transportation, would ensure better air quality, health, promoting the use of biofuels and other alternative energy sources. Industrial waste water or domestic wastewater household if not disposed of or treated with either will cause pollution. The high content of organic content in wastewater will lead to GHG emissionsÃ‚Â  impact on society as well as water pollution and odor pollution, Environmental Management in Industry Centers Adiwerna Tofu, Tegal regency was done by the management (cleaner production) and waste water treatment. Co Benefit analysis showed the relationship of environmental quality improvement occurs with the reduction of COD and capture methane gas that can be utilized for the community. The reduction of emissions in air can Ã‚Â reduce GHG. Method of estimated GHG reduction can be done by comparing GHG emissions before the project (baseline - BE) and after the implementation of projects co-benefits (project - PE). The evaluation was done by grouping into 3 tiers. Evaluation indicators are COD, BOD5, smell, CH4, while other indicators are Ã‚Â N, P and hazardous waste Ã‚Â indicators concerning health. To get the best results of the evaluation required complete data.Ã‚Â Keywords : GRK, Co-benefit,Tier, Metana, COD